Stone Matrix Asphalt Performance with Glycerin Pitch as Asphalt Binder Extender - Sihombing, Atmy Verani Rouly; Utami, Retno; Somantri, Andri Krisnandi; Febriansya, Aditia; Sihombing, Reza Phalevi; Mulyadi, Agah Muhammad (Periodica Polytechnica Civil Engineering, 2023)
This research aims to utilize glycerin pitch waste as an alternative asphalt binder (extender) in Stone Mastic Asphalt (SMA) mixture. Glycerin pitch (GP) is a by-product from crude glycerol refining process from the palm oil oleochemical industry. The research method was carried out by testing the chemical and physical characteristics of GP by comparing it to pen 60/70, then testing based on asphalt binder rheology and asphalt concrete characteristics. ANOVA statistical test and Tukey-Kramer statistical grouping test were used to know the significant use of GP in SMA mixture. The variations of GP content tested to pen 60/70 were 0%, 15% and 25% by weight, then used as a binder for the SMA mixture which was tested under asphalt content (Pb) conditions based on Marshall characteristic, immersion index and drain down. The test results show that GP has the potential as an asphalt extender, with a maximum content of 22% by weight of asphalt binder or with a ratio of 1 GP: 4 pen 60/70. The characteristics of the SMA mixture using pen 60/70 and GP as asphalt binder extender, under conditions of Pb = 7% produce SMA mixture that meets the specification. Statistically, in stability characteristics of SMA, GP has a significant effect on SMA + 22% GP mixture. In the immersion index, the use of GP has a significant effect on all type of mixture, while in the draindown characteristics has significant effect on the SMA+0% GP mixture.